2018
DOI: 10.1128/jvi.01912-17
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Replication Regulation by Acetylation of a Conserved Lysine in the E2 Protein

Abstract: iii ACKNOWLEDGEMENTS I would like to thank my supervisor Elliot J. Androphy for his guidance, and encouragement over these many years. I truly appreciate your faith and continuous support.I also want to thank all members of the Androphy lab, for your guidance, critiques, and support.Thank you to my thesis committee, without whom none of this would be possible.Your guidance has been invaluable. Michael Klemsz, Suk-Hee Lee, Lindsey Mayo, and Andy Yu. The Papillomavirus E2 protein is a sequence specific DNA bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 139 publications
(133 reference statements)
1
23
1
Order By: Relevance
“…HPV replication is dependent on acetylation at K111 by P300. Previous experiments suggested the regulatory role of E2 on PV replication by mutating lysine 111 to arginine, glutamine, and alanine (12). After confirming that Topo1 recruitment is P300 specific (Fig.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…HPV replication is dependent on acetylation at K111 by P300. Previous experiments suggested the regulatory role of E2 on PV replication by mutating lysine 111 to arginine, glutamine, and alanine (12). After confirming that Topo1 recruitment is P300 specific (Fig.…”
Section: Resultssupporting
confidence: 61%
“…We previously reported that the K111 E2 mutations did not alter E2 DNA binding or E1 recruitment to the replication origin. However, the K111R mutant was unable to induce origin unwinding and RPA accumulation (12). We suspected the requirement for Topo1 during replication because of the relevant functions and made two key discoveries.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…RNA (1 g) was used for cDNA synthesis using a SuperScript III first-strand synthesis system (Thermo Fisher Scientific). cDNA was analyzed by quantitative PCR for HPV18 E6 and actin using previously published primers (59).…”
Section: Methodsmentioning
confidence: 99%